2019
DOI: 10.1021/acs.jcim.9b00821
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Target Associations for Polypharmacology from Analysis of Crystallographic Ligands of the Protein Data Bank

Abstract: The design of a chemical entity that potently and selectively binds to a biological target of therapeutic relevance has dominated the scene of drug discovery so far. However, recent findings suggest that multitarget ligands may be endowed with superior efficacy and be less prone to drug resistance. The Protein Data Bank (PDB) provides experimentally validated structural information about targets and bound ligands. Therefore, it represents a valuable source of information to help identifying active sites, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 162 publications
0
17
0
Order By: Relevance
“…This type of search is expected to help identify novel potential multi-target ligands, based on the concept that structurally similar compounds could have similar biological activities ( 29 ). These results could also be useful to identify the more suitable protein conformation(s) for subsequent structure-based in silico polypharmacology design, as previously reported ( 13 , 15 , 23 ). Targets can be queried through their UniProt identifiers or names via a drop-down menu, which was designed to dynamically restrict the search upon the keyword typed in the dedicated input text box (Figure 2C ).…”
Section: The Ligadvisor Webservermentioning
confidence: 52%
See 2 more Smart Citations
“…This type of search is expected to help identify novel potential multi-target ligands, based on the concept that structurally similar compounds could have similar biological activities ( 29 ). These results could also be useful to identify the more suitable protein conformation(s) for subsequent structure-based in silico polypharmacology design, as previously reported ( 13 , 15 , 23 ). Targets can be queried through their UniProt identifiers or names via a drop-down menu, which was designed to dynamically restrict the search upon the keyword typed in the dedicated input text box (Figure 2C ).…”
Section: The Ligadvisor Webservermentioning
confidence: 52%
“…In a recent study ( 15 ), we performed extensive in silico investigations within the Protein Data Bank (PDB) ( 16 ), with the aim of identifying promising target combinations for polypharmacology. The results of this study allowed us to conclude that ligands reported within the PDB represent a reliable source of structural and biological information for multi-target drug design and repurposing ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the potential benefit in targeting HDAC6 and Hsp90 with dual-acting drug has garnered considerable interest from the scientific community. Rationally designing multi-target ligands is still a challenge, especially for targets as Hsp90 and HDAC6, which do not share significant binding site similarity [41][42][43][44]. However, computational approaches have proved to be of help in screening and selecting suitable candidates [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…10 A repurposing workflow integrating different computational approaches was implemented in order to increase the robustness of the adopted in silico protocol, 6 such a procedure having already demonstrated to increase the screening performances in polypharmacology contexts. 11 In particular, we firstly carried out extensive 2D fingerprint-and 3D shape-based similarity estimations on the investigated library of compounds against ligands with a known profile of activity, extracted from the DrugBank, Protein Data Bank and ChEMBL databases. [12][13][14] Interestingly, several targets emerged as valuable candidates for the repositioning of the compounds.…”
Section: Introductionmentioning
confidence: 99%